Analisis Unsur Intrinsik Pada Cerpen “Perempuan Terakhir” Karya M. Shoim Anwar dan Implementasi Pada Pembelajaran Bahasa Indonesia di SMA - Merdina Ziraluo; Helnanirma Susanti Fau; Agustinus Duha; Kalvintinus Ndruru; Anita Zagoto (Journal on Education, 2024)
Literary works are human creations born with beautiful language and capable of evoking emotional responses in readers and listeners. Literary works such as short stories are miniatures of life with various issues. In short stories, a fragment of a character's life is narrated, filled with conflicts, touching or pleasant events, and leaving unforgettable impressions. In the short story of "Perempuan Terakhir", there are intrinsic elements that become the object of research. This study aims to identify and discover the intrinsic elements in the short story "Perempuan Terakhir" by M. Shoim Anwar. The research method used is a qualitative research method with a descriptive approach. Based on the research results, it is explained that in the short story "Perempuan Terakhir" by M. Shoim Anwar, several intrinsic elements are found, such as theme, message, plot, characterization, characteristics, setting (place, time), point of view, and language style. Through literary learning in schools, intrinsic elements can provide knowledge benefits for students, where positive aspects can be applied through the attitudes of students both in the school environment and in the family environment. The suggestions given from this research are: (1) Teachers should teach students to analyze and identify the intrinsic elements contained in short stories, (2) For future researchers, to be able to analyze and identify the elements or values contained in literary works.